Evaluating Carbon Footprint in the Construction Industry: Challenges and Mitigation Strategies - Deupa, Jyoti; Bohara, Birendra Kumar (Far Western Review, 2025)
significantly to the world’s overall carbon footprint. It accounts for approximately 39-40% of total annual emissions, with about 27-28% stemming from operational emissions and 11-13% from embodied carbon (United Nations Environment Programme, 2019). These emissions have a serious impact on climate change and environmental degradation. Despite this, there is still a lack of effective strategies to fully eliminate carbon emissions in the sector. This study focuses on identifying the primary sources of carbon emissions in construction, examining their impact and exploring the challenges in implementing reduction measures. It adopts a qualitative research approach, utilizing document analysis to gather data through an extensive literature review. Findings indicate that emissions from the construction industry continue to rise. The main contributors of CO2 emissions include the extraction and processing of raw materials, manufacturing of construction products, transportation to construction sites, emissions generated during operation and demolition at the end of a building’s life cycle. Although both governmental and non- governmental organizations are actively working on policies to lower emission levels, the goal remains challenging. The World Green Building Council (WGBC) continues its ambitious mission to achieve a carbon-free construction sector by 2030. Strategies such as reducing material waste, using sustainable construction materials, adhering to green building standards and utilizing renewable energy sources offer promising solutions. However, among several challenges, top five challenges are high initial cost, shortage of material and skilled manpower, technology, lack of awareness and interest among stakeholders and government policies.